1993
DOI: 10.1259/0007-1285-66-791-998
|View full text |Cite
|
Sign up to set email alerts
|

Uterine sarcomas: a review of the Edinburgh experience from 1974 to 1992

Abstract: A retrospective review of patients treated for a uterine sarcoma in Edinburgh from 1974 to 1992 has been performed. Clinical details at presentation, tumour pathology, treatment and the outcome of treatment were all recorded. 82 patients' case notes were reviewed. 54 patients had died and 28 were alive (mean follow-up period 80.3 months). 39 patients had a malignant mixed mesodermal tumour, 12 patients had an endometrial stromal sarcoma, and 27 had a leiomyosarcoma. Using a modified FIGO staging retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
13

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 10 publications
2
26
0
13
Order By: Relevance
“…As in endometrial cancer it has been observed that in US survival relates to initial stage [1,5,9]. In common with these data we observed an improved prognosis for low stage and especially for low histological tumor grad ing.…”
Section: Radiotherapy Of Uterine Sarcomassupporting
confidence: 88%
See 3 more Smart Citations
“…As in endometrial cancer it has been observed that in US survival relates to initial stage [1,5,9]. In common with these data we observed an improved prognosis for low stage and especially for low histological tumor grad ing.…”
Section: Radiotherapy Of Uterine Sarcomassupporting
confidence: 88%
“…From the data in the literature there is no prospective randomized trial available to demonstrate improved sur vival after XRT for any type of US in the long term [6,7,9], In our series we found an increased overall survival at 5 years in group B as compared to group A (90% group B vs. 34% group A). The positive results in our analysis however might at least partially be biased by the high pro portion of patients with ESS in group B of whom neither in group A nor group B relapsed.…”
Section: Leiomyosarcomamentioning
confidence: 40%
See 2 more Smart Citations
“…Representan un grupo heterogéneo de neoplasias que se desarrollan del miometrio (leiomiosarcomas) y desde la mucosa uterina (sarcomas del estroma endometrial y sarcomas mesodér-micos mixtos) (2). Tienen un pronóstico pobre con una sobrevida global en general menor del 50% a 2 años, incluso en etapas tempranas de la enfermedad (3,4,5). Debido a la rareza de este tumor, así como también a su diversidad patológi-ca no existen estudios prospectivos randomizados fase III, por lo que las recomendaciones de tratamiento deben ser basadas en revisiones retrospectivas de pequeñas series, lo que asociado a su mal pronóstico hacen difícil su manejo clínico.…”
Section: Introductionunclassified